2022
DOI: 10.1186/s12872-022-02776-6
|View full text |Cite
|
Sign up to set email alerts
|

Is cell regeneration and infiltration a double edged sword for porcine aortic valve deterioration? A large cohort of histopathological analysis

Abstract: Background and objective Bioprostheses are the most common prostheses used for valve replacement in the Western medicine. The major flaw of bioprostheses is the occurrence of structural valve deterioration (SVD). This study aimed to assess the pathological features of porcine aortic valve (PAV)-SVD based on histomorphological and immunopathological characteristics of a large cohort of patients. Methods Histopathological data of 109 cases with resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…In our study, the strong cellular immune response against human pericardium was observed in the absence of an induced anti-carbohydrate antibody response as determined by our assay with PAEC. This is consistent with the direct activation of macrophages, lymphocytes, and platelets by glutaraldehyde tissue fixation [35].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our study, the strong cellular immune response against human pericardium was observed in the absence of an induced anti-carbohydrate antibody response as determined by our assay with PAEC. This is consistent with the direct activation of macrophages, lymphocytes, and platelets by glutaraldehyde tissue fixation [35].…”
Section: Discussionsupporting
confidence: 88%
“…Notably, macrophages and lymphocytes have also been observed in BHV retrieved from patients [34,35]. The mechanisms responsible for the immune infiltrates in SVD are not fully understood, but various pathways have been proposed, including the release of proteolytic enzymes and reactive oxygen species [12][13][14][15]35,36]. In the present study, the samples that displayed a prominent and penetrating cellular immune infiltrate were associated with more severe structural alterations.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Recently, we described that glutaraldehyde-treated bovine pericardium inside a bioprosthetic artificial heart was quickly recovered by fibrin and newly formed endothelial cells ( 6 , 7 ). Although explanted BHVs are infiltrated by inflammatory cells but also fibrotic and endothelial cells ( 8 , 9 ), their involvement in SVD is always a question of debate.…”
Section: Introductionmentioning
confidence: 99%